The effect of self management on consumptive behavior in students - Asni Asni; Najma Mega Wangi; Nur Aini (Jurnal Konseling dan Pendidikan, 2021)
This research is motivated by the existence of consumptive behavior among students. This condition occurs because students tend to respond to various changes in the world of fashion. Consumptive behavior can be overcome by increasing self-management to control consumptive behavior. This study aims to determine the effect of self-management on consumptive behavior. The research method used is a quantitative method using a simple random sampling technique to 95 students. The instruments used were consumptive behavior instruments and self-management instruments. The number of instrument items used was 75 items that met the requirements for the validity and reliability of the instrument. Analysis of the data used in this study using inferential statistical analysis.